Deco: A Decentralized, Cooperative Atomic Commit Protocol - Daniel J. Buehrer; Chun-Yao Wang (Journal of Computer Networks and Communications)
An atomic commit protocol can cause long-term locking of databases if the coordinator crashes or becomes disconnected from the network. In this paper we describe how to eliminate the coordinator. This decentralized, cooperative atomic commit protocol piggybacks transaction statuses of all transaction participants onto tokens which are passed among the participants. Each participant uses the information in the tokens to make a decision of when to go to the next state of a three-phase commit protocol. Transactions can progress to ensure a uniform agreement on success or failure, even if the network is partitioned or nodes temporarily crash.